A Cognitive View of Reading Comprehension: Implications for Reading Difficulties. Issue 1 (February 2014) - Kendeou, Panayiota; van den, Paul; Helder, Anne; Karlsson, Josefine
<x xml:space="preserve">Abstract</x> Our aim in the present paper is to discuss a "cognitive view" of reading comprehension, with particular attention to research findings that have the potential to improve our understanding of difficulties in reading comprehension. We provide an overview of how specific sources of difficulties in inference making, executive functions, and attention allocation influence reading comprehension processes and outcomes and may lead to reading comprehension problems. Finally, we discuss how the consideration of these potential sources of difficulty have practical implications for the design and selection of instructional materials.